Atomic Force Microscopy of the Structure of Red Blood Cell Membranes in Acute Blood Loss and Reinfusion - V. V. Moroz; A. M. Chernysh; Ye. K. Kozlova; A. K. Kirsanova; I. S, Novoderzhkina; V. V. Aleksandrin; P. Yu. Borshchegovskaya; U. A. Bliznyuk; R. M. Rysayeva (Общая реаниматология)
Objective: to examine the surface heterogeneities of red blood cell membranes after acute massive blood loss and blood reinfusion, by using atomic force microscopy (AFM). Materials and methods. Experiments were carried out under nembu-tal anesthesia on male rats. Hypovolemic hypotension was induced during 60 minutes, followed by blood reinfusion. The experimental phases were as follows: control before blood loss; 5 minutes after its onset; 1 hour following hypotension; and 1 and 3 hours after reinfusion. Membrane surface images were obtained by AFM in the constant scanning mode. Spatial surface spectral transformation was used. Results. The nano-surface parameters were shown to be intrinsic characteristics of membranes. The greatest changes occurred at the early stages of transient processes: blood loss and reinfusion. Conclusion. The application of AFM permitted the authors to trace the time course of changes in the red blood cell membrane surfaces during acute total blood loss and further blood reinfusion to tolerances of fractions of nanometer. Key words: blood loss, reinfusion, nanostructure, atomic force microscopy.